Copper chelation in patients with hypertrophic cardiomyopathy. Issue 1 (15th February 2022) - Reid, Anna; Miller, Christopher; Farrant, John Peter; Polturi, Rahul; Clark, David; Ray, Simon; Cooper, Garth; Schmitt, Matthias
Abstract : Background: Disturbances of copper (Cu) homeostasis can lead to hypertrophic cardiac phenotypes (eg, Wilson's disease). We previously identified abnormal Cu homeostasis in patients with hypertrophic cardiomyopathy (HCM) and, therefore, hypothesised that Cu 2+ –selective chelation with trientine dihydrochloride may slow or reverse disease progression in HCM. The aim of this study was, therefore to explore the clinical efficacy, safety and tolerability of trientine in HCM. Methods: In this medicines and healthcare products regulatory agency (MHRA) registered open-label pilot study, we treated 20 HCM patients with trientine for 6 months. Patients underwent a comprehensive assessment schedule including separate cardiac magnetic resonance imaging (CMR) and CMR 31 P-spectroscopy at baseline and end of therapy. Predefined end points included changes in left ventricular mass (LVM), markers of LV fibrosis, markers of LV performance and myocardial energetics. Ten matched patients with HCM were studied as controls. Results: Trientine treatment was safe and tolerated. Trientine caused a substantial increase in urinary copper excretion (0.42±0.2 vs 2.02±1.0, p=0.001) without affecting serum copper concentrations. Treatment was associated with significant improvements in total atrial strain and global longitudinal LV strain using both Echo and CMR. LVM decreased significantly in the treatment arm compared with the control group (−4.2 g v 1.8 g, p=0.03). A strong trend towards an absolute decrease in LVM was observed in the treatment group (p=0.06). These changes were associated with a significant change in total myocardial volume driven by a significant reduction in extracellular matrix (ECM) volume (43.83±18.42 mL vs 41.49±16.89 mL, p=0.04) as opposed to pure cellular mass reduction and occurred against a background of significant ECM volume increase in the control group (44.59±16.50 mL vs 47.48±19.30 mL, p=0.02). A non-significant 10% increase in myocardial phosphocreatine/adenosine triphosphate (PCr/ATP) ratio with trientine therapy (1.27±0.44 vs 1.4±0.39) was noted. Conclusions: Cu 2+ –selective chelation with trientine in a controlled environment is safe and a potential future therapeutic target. A phase 2b trial is now underway.